2019
DOI: 10.1002/mrd.23153
|View full text |Cite
|
Sign up to set email alerts
|

The seminal acrosin‐inhibitor ClTI1/SPINK2 is a fertility‐associated marker in the chicken

Abstract: The seminal plasma is a very complex fluid, which surrounds sperm in semen. It contains numerous proteins including proteases and protease inhibitors that regulate proteolytic processes associated with protein activation and degradation. We previously identified a seminal protein, chicken liver trypsin inhibitor 1 (ClTI‐1) over expressed in semen of roosters with high fertility, suggesting a role in male fertility. In the present study, we showed that ClTI‐1 gene is actually SPINK2. Using normal healthy adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Its more-abundance in the seminal plasma of LSM roosters make us speculate that failure of SPINK2 to bind to the membrane and acrosome of the damaged and disfunction spermatozoa. In a previous study, SPINK2 was reported to be more-abundant in the seminal plasma of roosters with high fertility (6,29). This inconstancy might be due to the different causal factors between studies.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Its more-abundance in the seminal plasma of LSM roosters make us speculate that failure of SPINK2 to bind to the membrane and acrosome of the damaged and disfunction spermatozoa. In a previous study, SPINK2 was reported to be more-abundant in the seminal plasma of roosters with high fertility (6,29). This inconstancy might be due to the different causal factors between studies.…”
Section: Discussionmentioning
confidence: 92%
“…Seminal SPINK2, also named chicken liver trypsin inhibitor 1 (ClTI-1) (29), originates from testis, epididymis, and genital tract. It functions as an Chicken Sperm Motility Related Seminal Plasma Proteins 27 acrosin/trypsin inhibitor protecting the spermatozoa against damage by binding to the sperm membrane (29). Its more-abundance in the seminal plasma of LSM roosters make us speculate that failure of SPINK2 to bind to the membrane and acrosome of the damaged and disfunction spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acrosin inhibitor is produced by accessory sexual glands and secreted in the seminal plasma of ruminants (Cechová & Fritz, 1; Cechová, Jonáková, Sedláková, & Mach, ; Codognoto et al, ; Davidová, Jonáková, & Manásková‐Postlerová, ; Martins et al, ; Torska & Strzezek, ; Tschesche, Kupfer, Klauser, Fink, & Fritz, ), and it functions to prevent early sperm proteolysis induced by acrosin, an acrosomal enzyme responsible for zona pellucida hydrolysis during acrosomal reaction and fertilization (Adham, Nayernia, & Enzel, ; Crosby, Jones, Barros, & Carvalho, ; Gurupryaia et al, ; Martins et al, ). Acrosin inhibitor and acrosin are proteins related to in vivo and in vitro fertility in humans (Goodpasture, Zavos, Cohen, & Zaneveld, ; Kennedy, Reid, Kaminski, Jeyendran, & Zaneveld, ; Mohsenian, Syner, & Moghissi, ) and chickens (Thélie et al, ). In fact, the upregulation of acrosin inhibitor in cattle can contribute to cell protection during cryopreservation, since cold shock is able to induce acrosomal morphological alterations (Quinn & White, 1), and enzyme loss can damage the spermatozoa and fertility in boar (Johnson & Pursel, ) and bovine (Church & Graves, ).…”
Section: Discussionmentioning
confidence: 99%